Dear (Legal) Ed: One Indigenous Scholar's Reflections on 30 years of Interactions with Legal Education - Danielle Lussier (Legal Education Review)
In this work, the author, a Red River Métis legal scholar, mobilizes autoethnographic and Indigenous Women’s Life Writing research methods to speak back to her experiences in legal education that span over three decades. Engaging with literature on the struggles of Indigenous learners and academics labouring within the Canadian Legal Academy, she reflects on colonial legal education, gendered glass ceilings and steel doors, and systemic anti-Indigenous racism that continues to act as a barrier to meaningful reconciliation in legal education in Canada.